Gastroschisis Is Associated With Placental Delayed Villous Maturation. (June 2020) - Ruschkowski, Brittany; Lafreniere, Anthea; Demellawy, Dina El; Grynspan, David
Gastroschisis is a congenital abnormality characterized by visceral herniation through an abdominal wall defect. While the cause of gastroschisis is unknown, it has been linked to risk factors including young maternal age, smoking, and alcohol use during pregnancy. To date, the only established placental correlate is amniocyte vacuolization. Based on our clinical experience, we hypothesized that delayed villous maturation (DVM) is also associated with gastroschisis. We conducted a retrospective slide review of 23 placentas of neonates with gastroschisis. Additionally, we selected 2 control groups of placentas: 1 with a previous diagnosis of DVM and 1 with normal villous morphology. All placentas were randomized and reviewed by 2 perinatal pathologists, who were blinded to the group; DVM and amniocyte vacuolization were assessed. Gastroschisis was associated with increased placental DVM in 65.2% of cases (vs 13.6% of controls; P = .0007) and increased amniocyte vacuolization in 52.2% of cases (vs 9.1% of controls; P = .003) compared to the control group. Based on the normal and DVM groups, kappa agreement between current slide review and initial pathology diagnosis was 0.419, indicating moderate agreement. Our study shows that gastroschisis is associated with placental DVM. This association may be due to (1) a common upstream factor contributing to both gastroschisis and DVM or (2) DVM may be a consequence of the altered placental and amniotic environment in the context of gastroschisis.